2020
DOI: 10.1016/j.jksues.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Teleoperated robotic arm movement using electromyography signal with wearable Myo armband

Abstract: The main purpose of this research is to move the robotic arm (5DoF) in real-time, based on the surface Electromyography (sEMG) signals, as obtained from the wireless Myo gesture armband to distinguish seven hand movements. The sEMG signals are biomedical signals that estimate and record the electrical signals produced in muscles through their contraction and relaxation, representing neuromuscular activities. Therefore, controlling the robotic arm via the muscles of the human arm using sEMG signals is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 27 publications
0
32
0
2
Order By: Relevance
“…The studies based on feature extractions proposed across TD, FD and TFD shows the best results using the TD EMG feature. Hudgins [34] proposed the four different time-domain features (MAV, WL, ZC, SSC) [35] for feature extraction from EMG, and it is the most adopted one to date in the field of myoelectric pattern recognition [11]. Willison amplitude (WAMP) [36], Autoregressive (AR) model parameters [37] and time domain-auto regression (TD-AR) are also used to extract feature information.…”
Section: Pattern Recognition-based Myoelectric Controlmentioning
confidence: 99%
“…The studies based on feature extractions proposed across TD, FD and TFD shows the best results using the TD EMG feature. Hudgins [34] proposed the four different time-domain features (MAV, WL, ZC, SSC) [35] for feature extraction from EMG, and it is the most adopted one to date in the field of myoelectric pattern recognition [11]. Willison amplitude (WAMP) [36], Autoregressive (AR) model parameters [37] and time domain-auto regression (TD-AR) are also used to extract feature information.…”
Section: Pattern Recognition-based Myoelectric Controlmentioning
confidence: 99%
“…The IMU bracelet weighs 93 grams with an adjustable diameter of 12.5-38.4 cm; none of the eight participants reported that the device caused any significant impediment their optimal performance. The hardware includes eight medical-grade stainless steel EMG sensors which report raw electrical muscle activity in a voltage range of 0-2 mV expressed in oscillations of −1 to 1 (Hassan et al, 2019). Two battery cells are embedded with a capacity of 260 mA/hr and an operating voltage range of 1.7 to 3.3 V. A three-axis gyroscope records angular velocity in degrees of change in radians per second, and a three-axis accelerometer as an estimation of −8 to 8 g (1 g = 9.81 m/s 2 ).…”
Section: Data Acquisition and Synchronizationmentioning
confidence: 99%
“…Other classification techniques based in ML are used for gestures and movement identification, obtaining better results than other traditional methods [ 59 , 60 , 61 , 62 ], despite presenting some disadvantages such as the lack of transparency in the determination of results [ 12 ].…”
Section: Signal Analysismentioning
confidence: 99%
“…Hassan et al [ 62 ] used a Myo bracelet, with eight channels taken from the forearm, to classify seven proposed hand movements. The proposed movements are used to control a robotic arm using inexpensive hardware.…”
Section: Signal Analysismentioning
confidence: 99%